The Role of Physical Activity in Male Reproductive Health – A Systematic Review - Joanna Prus; Klaudia Łuczak; Hanna Sitarek; Adrianna Tabeau; Patryk Dudek; Wiktoria Ulicka; Marcel Chudzikowski; Justyna Pięta; Agnieszka Pawlik; Agata Prokopiuk (Journal of Education, Health and Sport)
Introduction and purpose: Nowadays infertility is an important problem, which affects even 17,5% couples during their lifetime. There are many factors playing a role in the development of infertility, among others the ones connected with lifestyle. There are many studies analysing lifestyle influence on the male reproductive health. The aim of this article is to review available literature concerning physical activity and to analyse its impact on male fertility, considering different exercise-related mechanisms, which may cause impairments.